Tenecteplase Thrombolysis in Posterior Circulation Stroke - Alemseged, Fana; Campbell, Bruce C. V. (Frontiers in Neurology, 2021)
One in five ischaemic strokes affects the posterior circulation. Basilar artery occlusion is a type of posterior circulation stroke associated with a high risk of disability and mortality. Despite its proven efficacy in ischaemic stroke more generally, alteplase only achieves rapid reperfusion in 4% of basilar artery occlusion patients. Tenecteplase is a genetically modified variant of alteplase with greater fibrin specificity and longer half-life than alteplase, which can be administered by intravenous bolus. The single-bolus administration of tenecteplase vs. an hour-long alteplase infusion is a major practical advantage, particularly in “drip and ship” patients with basilar artery occlusion who are being transported between hospitals. Other practical advantages include its reduced cost compared to alteplase. The EXTEND-IA TNK trial demonstrated that tenecteplase led to higher reperfusion rates prior to endovascular therapy (22 vs. 10%, non-inferiority p = 0.002, superiority p = 0.03) and improved functional outcomes (ordinal analysis of the modified Rankin Scale, common odds ratio 1.7, 95% CI 1.0–2.8, p = 0.04) compared with alteplase in large-vessel occlusion ischaemic strokes. We recently demonstrated in observational data that tenecteplase was associated with increased reperfusion rates compared to alteplase prior to endovascular therapy in basilar artery occlusion [26% (n = 5/19) of patients thrombolysed with TNK vs. 7% (n = 6/91) thrombolysed with alteplase (RR 4.0 95% CI 1.3–12; p = 0.02)]. Although randomized controlled trials are needed to confirm these results, tenecteplase can be considered as an alternative to alteplase in patients with basilar artery occlusion, particularly in “drip and ship” patients.